2020
DOI: 10.1007/s00432-020-03240-8
|View full text |Cite
|
Sign up to set email alerts
|

Primary tumor standardized uptake value (SUVmax) measured on 18F-FDG PET/CT and mixed NSCLC components predict survival in surgical-resected combined small-cell lung cancer

Abstract: Purpose The combined small-cell lung cancer (c-SCLC) is rare and has unique clinicopathological futures. The aim of this study is to investigate 18 F-FDG PET/CT parameters and clinicopathological factors that influence the prognosis of c-SCLC. Methods Between November 2005 and October 2014, surgical-resected tumor samples from c-SCLC patients who received preoperative 18 F-FDG PET/CT examination were retrospectively reviewed. The maximum standardized uptake value (SUV max), metabolic tumor volume (MTV) and tot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 49 publications
1
2
0
Order By: Relevance
“…Previous studies had proposed some factors that were potentially correlated with OS of C-SCLC, including smoking history, 10 extensive-stage disease, 11 lymph node metastasis, 2 , 8 adjuvant treatment, 2 , 10 , 11 and pathologically combined LCNEC 10 and SCC. 17 Lei et al reported that lymph node metastasis was significantly correlated with decreased disease-free survival (DFS) and OS in surgically resected C-SCLC, consistent with our finding. 9 In addition, in a previously published study, Men et al observed that positive lymph nodes ratio >10% was an independent risk factor of OS for these patients.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Previous studies had proposed some factors that were potentially correlated with OS of C-SCLC, including smoking history, 10 extensive-stage disease, 11 lymph node metastasis, 2 , 8 adjuvant treatment, 2 , 10 , 11 and pathologically combined LCNEC 10 and SCC. 17 Lei et al reported that lymph node metastasis was significantly correlated with decreased disease-free survival (DFS) and OS in surgically resected C-SCLC, consistent with our finding. 9 In addition, in a previously published study, Men et al observed that positive lymph nodes ratio >10% was an independent risk factor of OS for these patients.…”
Section: Discussionsupporting
confidence: 92%
“…1 Numerous studies also explored the effect of postoperative radiotherapy on the OS of C-SCLC. 2,8,11,17,24 In a study conducted by Men et al, they indicated that postoperative chemotherapy was not significantly correlated with improved OS of C-SCLC. 24 However, subgroup analysis revealed that postoperative chemotherapy significantly improved the survivals of patients with stage III or N2 disease.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation